Dual Vocational Training in Aragón: A Corporate View of the Dependent Care Sector - Virginia Domingo Cebrián (Universidad Autónoma de Baja California, 2021)
Dual Vocational Training (FPD) was recently introduced in Spain and is gradually becoming well established. This research focuses on Aragón, and in particular on companies operating in the dependent care sector, and aims to examine the state of Dual Vocational Training in the "sociocultural and community services" occupational category, from the perspective of participating companies; identify the facilitators and limitations of this system; and show the main impacts of dual Vocational Training on participating companies. A quantitative methodology was employed, based on an electronic questionnaire. The results show that companies find Dual Vocational Training to be positive and satisfactory, and that it is not too costly and offers a way to recruit and help train professionals.